Teachers’ perceptions about oral corrective feedback and their practice in efl classrooms (2012)
Corrective feedback has been discussed mainly in second language acquisition contexts, but less has been done concerning corrective feedback in foreign language settings. In this descriptive study, conducted at a Mexican university, our aims were to identify the perceptions of instructors of English as a foreign language about corrective feedback and its actual practice in their classrooms. A semistructuredinterview and a questionnaire were used to collect the data. The results show that teachers in general have a positive perception of oral corrective feedback. However, some consider it as optional because instructors are very concerned with students’ feelings and emotions. Unfocused oral corrective feedback and implicit strategies are predominant in practice. Corrective feedback provided bythe instructor is preferred to that provided by peers. Self-correction is the least popular.La retroalimentación correctiva se ha discutido principalmente en contextos de adquisición de segundas lenguas, pero poco se ha hecho en el área de lenguas extranjeras. Esta investigación descriptiva, realizada en una universidad mexicana, tuvo como objetivo identificar las percepciones de profesores de inglés como lengua extranjera sobre retroalimentación correctiva y su práctica. Para la recolección de datos se usaron una entrevista semiestructurada y un cuestionario. Los resultados muestran que si bien los profesores en general tienen una percepción positiva sobre la retroalimentación correctiva oral, algunos la consideran opcional, pues les preocupan los sentimientos y emociones de los estudiantes. En la práctica predominan la retroalimentación correctiva oral no enfocada y lasestrategias implícitas. Asimismo, se prefiere la retroalimentación correctiva que ofrece el docente y laautocorrección es la menos común.